Utopia [compact disc] - Santos, Romeo, 1981-; Santos, Romeo, 1981- (Sony Music Latin, 2019)
Romeo Santos, one of the biggest stars in Latin music, releases his fourth solo studio album. The first single, Inmortal, made headlines. It features a reunion of the group Aventura, which he was a member of.